Multivariate analysis of biometric traits and their shared variance in Chhattisgarhi buffalo - VOHRA, VIKAS; SINGH, MOHAN; DAS, RAMENDRA; CHOPRA, ALKA; KATARIA, R S (The Indian Journal of Animal Sciences, 2017)
Principal component analysis (PCA) with a varimax rotation was applied to 18 highly inter-correlated body biometric traits in 157 adult female water buffalo from Chhattisgarh state of India to deduce the components that control body conformation, suitable for use in buffalo breeding, and to reveal the main sources of their shared variability. First principal component explained 34.47% of total variance in body biometric traits and can be used in the evaluation and comparison of body morphology in female water buffaloes using body height, neck circumference, rump width, leg length, paunch girth, chest girth and tail length. The shared variability due to common variance ranged from 92% (horn length) to 51% (rump length) whereas 8 to 49% of their variation was contributed by unique variance specific for each trait in Chhattisgarhi buffaloes.